Uh and um as pragmatic markers in dialogues: a contrastive perspective on the functions of planners in fiction and conversation - Tonetti Tübben, Ilenia; Landert, Daniela (Contrastive pragmatics, 2022)
Abstract The planners uh and um fulfil a range of interpersonal and discursive functions, akin to other pragmatic markers. Although there appear to be differences between the planners’ functions across genres, the factors influencing these differences have not been analysed comprehensively so far. In our study, we analyse the frequency and functions of uh and um across three different genres: spontaneous conversation, scripted dialogues in television series and dialogues in improvised theatre. Our findings suggest that both the fictional nature of a text and its degree of composition have an influence on the planners’ functions. Our results confirm that planners are indeed pragmatic markers which serve a range of textual and interpersonal functions, and that the frequency and functions of planners are affected by factors relating to the context of language production, which include spontaneity as well as the content and function of a text.
Gesehen am 04.04.2024